2015
DOI: 10.4209/aaqr.2015.02.0110
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Diversity and Carbon Storage in Air Quality Enhancement Zones in Taiwan

Abstract: Taiwan had established air quality enhancement zones (AQEZs) by planting trees, aiming to improve air quality and ecological environment. Trees in the AQEZs reduce the amount of carbon dioxide in the atmosphere by storing carbon in their tissues. Species diversity is a critical factor influencing the capacity of trees to capture carbon. In this study, we assessed tree species diversity and estimated the carbon storage of AQEZs of 98 sampling plots located in four regions. The zones examined contained 210 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In a study by Liu et al [17], they investigated the sensitivity of ground-level ozone concentrations to temperature variation in Taiwan using multiple regression models, indicating a positive correlation between ozone sensitivity and temperature. In order to improve air quality by planting trees, Wang et al [18] reported the benefits of air quality enhancement zone establishments in Taiwan, including CO 2 capture, carbon storage, and global warming mitigation. On the other hand, Li et al [19] evaluated the prospective impacts of electric vehicle (EV) penetration on the air quality in Taiwan because the traditional fuel-based vehicles greatly contributed to the emissions of criteria air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Liu et al [17], they investigated the sensitivity of ground-level ozone concentrations to temperature variation in Taiwan using multiple regression models, indicating a positive correlation between ozone sensitivity and temperature. In order to improve air quality by planting trees, Wang et al [18] reported the benefits of air quality enhancement zone establishments in Taiwan, including CO 2 capture, carbon storage, and global warming mitigation. On the other hand, Li et al [19] evaluated the prospective impacts of electric vehicle (EV) penetration on the air quality in Taiwan because the traditional fuel-based vehicles greatly contributed to the emissions of criteria air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of tree species for urban forests must be undertaken strategically to optimize the ecosystem benefits they provide (Morgenroth et al 2016). Trees within urban environments are essential in the reduction of the heat island effect (Hardin & Jensen 2007), reduction in air pollution (Escobedo et al 2011), infiltration of rainwater (Xiao & McPherson 2003), reduction of runoff, saving of electrical energy (Simpson & McPherson 1997), habitat, generation of feelings of well-being among people (Ulrich 1986), and biodiversity and carbon sequestration (Chiesura 2004, Wang et al 2015. However, there is a need to select suitable tree species under the proposed "10-20-30 rule" which establishes not to exceed 10% of a single species, 20% of the same genus, and 30% of the same family in an urban forest to promote the tree benefits (Santamour 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, forest ecosystems play important roles in reducing the atmospheric carbon dioxide and hence regulating climate change [13,14,15]. Thus, forests are among the vital components of the global ecosystems in addressing climate change, the most pressing issue in the world today [8,16,17]. Although forests are important sources or sinks of carbon, they are frequently affected by human activities pressure [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbon storage in grasslands ecosystems [40,44], carbon storage in the tropical forests [34,35], land use changes and carbon emissions in terrestrial ecosystems [18,21]. Other studies include land use changes, carbon sequestration and biodiversity [17,22,31,46] and carbon storage in plantations [6,33], while allometric models for species located in the coastal zone of Tanzania have been presented in [43]. Across all these studies, it is indicated that trees play a big role in carbon storage.…”
Section: Introductionmentioning
confidence: 99%